PENANGANAN KELUHAN PUBLIK DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA UTARA (STUDI PADA PELAYANAN E-KTP) - RATUWALANGON, FONNY; Tulusan, Femmy; Londa, Very (Sam Ratulangi University, 2017)
Abstract : Some government-issued regulations to handle and provides a variety of complaints into thesystem of complaints should be cared for properly in various government agencies managing the complaintshould have been look well in various government agencies. In order that the functions of the managementof complaints it could run well in order to improve the quality of existing services. The problems inherentin the grip of a public complains on the service of E-KTP in the service of the population and civilregistration distric of Minahasa Utara can be grouped into three types of complaints. First, complaint aboutthe delay of the process, Second, the unfriendly officers, third unclear information.This research uses qualitative research methods, descriptive. informant research by as much as 10(ten) informant: 1 person head of Department, 1 Secretary, 3 civil State apparatus, 5 people community.data collection techniques used i.e., interview techniques, techniques of observation/observation, andtechnical documentation. data analysis techniques used, namely the reduction of data, data presentation,and conclusion.Keywords: Public Complain, Service of E-KTP